Pengembangan Bahan Ajar Statistika Bermuatan Soal Literasi Numerasi Bernuansa STEM untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik pada PBL - Ahmad Musyafak; Arief Agoestanto (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2022)
The research objective is to develop statistical teaching materials containing STEM nuanced numeracy literacy questions to improve appropriate, practical and effective critical thinking skills used in learning. The type of research is research and development (RnD) using a 4D development model including define, design, develop, and disseminate. This research instrument uses a questionnaire to determine the feasibility and practicality as well as a critical thinking ability test to test the effectiveness of the teaching materials developed. This research uses the PBL model to determine the practicality and effectiveness of teaching materials. The research subjects were students of class VIII A at SMP Negeri 40 Semarang. The results showed that the feasibility of the developed teaching materials obtained very feasible criteria, and was very practical to use. The results of the effectiveness through the pretest-posttest, the proportion of students who complete learning is more than 74.5%, the posttest average is more than the pretest, and there is an increase in students' critical thinking skills after using the developed teaching materials, so it can be concluded that the developed teaching materials have feasible, practical, and effective to improve students' critical thinking skills in PBL model learning.